Estudo físico-químico da atividade fungicida de derivados anfifílicos de quitosana contra fungos do gênero Aspergillus : interação com modelos de membranas - Takaki, Mirelle [UNESP] (2015)
In this work is described the synthesis, characterization and study of antimicrobial properties of amphiphilic derivatives of chitosan against Aspergillus flavus. Deacetylated chitosan was obtained from the heterogeneous deacetylation of the commercial chitosan. The degree of deacetylation was determined by Hydrogen Nuclear Magnetic Resonance and the result was 97.3%. Molecular weights of commercial and deacetylated chitosans were determined by gel permeation chromatography and the obtained values were 338.46 kDa and 137.12 kDa, respectively. The hydrophobic derivatives were synthesized by a reductive amination reaction with dodecylaldehyde followed by reduction with sodium cyanoborohydride. Next increasing proportions of the quaternary group pentyltrimethylammonium was inserted on hydrophobic derivative. The degrees of substitution by dodecyl (4.0%) and pentyltrimethylammonium groups (4.8, 12.7 and 46.3%) were determined by Hydrogen Nuclear Magnetic Resonance. All synthesized derivatives were tested in vitro against Aspergillus flavus at increasing concentrations. The results showed that the modified derivatives with pentyltrimethylamonnium and dodecyl groups are more effective in inhibiting the growth of the fungus Aspergillus flavus when compared to deacetylated chitosan and the presence of hydrophobic groups in the polymer chain provides a stronger interaction with the cell membrane. The results of studies with model membranes agreed with the results of microbiological tests, showing that the presence of hydrophobic groups in chitosan backbone increases the interaction with lipid vesicles resulting in an increase in vesicles diameter and zeta potential. At first, it can be postulated that the mechanism of chitosan action against fungi is favored by hydrophobic interactions between chitosan derivatives and membrane lipids and may involve the adsorption on the cell wall and cell membrane disruption...